The "Patman Effect" and Stabilization Policy - Driskill, Robert A.; Sheffrin, Steven M. (Quarterly Journal of Economics, 1985)
This paper examines the controversial link between interest rates and prices by introducing interest costs into John Taylor's model of overlapping wage contracts. We find that the presence of interest costs does affect the stabilization process and can make the tradeoffs between output and price variability less favorable.